Mutual coupling reduction of dual port antenna using zero index metasurface structure - Ullah, M.H.; Wan Mahadi, W.N.L.; Latef, T.A.; Islam, M.T.; Uddin, M.J.; Ahsan, M.R. (IOS Press, 2015)
The design and prototyping of a dual port planar printed quad band/Ultra wide band (UWB) patch antenna, with octagonal ring shaped metasurface structure (MSS) assimilated at the back to reduce mutual coupling between antenna elements, is presented. The proposed MSS incorporated UWB antenna has been designed and fabricated on a high permittivity (r15) ceramic filled biopolymer based sandwich structured dielectric substrate. Substantial reductions of mutual coupling (S21) between the dual port array elements of the proposed antenna has been achieved by assimilating a 6 × 9 octagonal ring shaped metasurface structure with near zero refractive index (NZRI) in the ground plane. Measurement results show that the proposed antenna with MSS loading has achieved the reflection co-efficient (S11 <-10 dB) bandwidths of 1.25 (2.25-3.5) GHz, 1 (4-5) GHz, 0.7 (5.9-6.6) GHz and 1.75 (7.7-9.45) GHz. Stable radiation patterns, with gains of 3.18 dBi, 2.96 dBi, 3.34 dBi and 9.61 dBi, have been measured at resonant frequencies of 2.85 GHz, 4.4 GHz, 6.2 GHz and 8.75 GHz.